Behavioral psychology study of the main character in Room (2015) film - Wati, Nurhaliza Fajar; Muhajir, Fatimah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This study aims to explain the behavior of the main character, Jack, in the film Room (2015) using the behaviorist theories of John B. Watson and B.F. Skinner. The research uses a qualitative descriptive method with a behaviorist psychological approach. Data were collected through repeated viewing of the film, note taking, and identification of behavioralpatterns related to stimulus and response. The analysis focuses on classical conditioning, operant conditioning, and internal factors that influence behavior. The results of the study indicate that Jack’s behavior is shaped by various external stimuli, including conditioned responses to daily routines and social interactions within his limited environment. Operant conditioning is evident through Jack’s behavioral changes in response to consequences and rewards. Additionally, internal factors such as emotions, self-awareness, drives, and goal and intentions play a significant role in Jack’s responses and adaptation to his environment. These findings support the behaviorist perspective that human behavior is shaped and learned through interactions with the environment.